ASIC2 subunits facilitate expression at the cell surface and confer regulation by PSD-95. - Anne Marie S Harding; Nobuyoshi Kusama; Tomonori Hattori; Mamta Gautam; Christopher J Benson (PLoS ONE)
Acid-sensing ion channels (ASICs) are Na+ channels activated by changes in pH within the peripheral and central nervous systems. Several different isoforms of ASICs combine to form trimeric channels, and their properties are determined by their subunit composition. ASIC2 subunits are widely expressed throughout the brain, where they heteromultimerize with their partnering subunit, ASIC1a. However, ASIC2 contributes little to the pH sensitivity of the channels, and so its function is not well understood. We found that ASIC2 increased cell surface levels of the channel when it is coexpressed with ASIC1a, and genetic deletion of ASIC2 reduced acid-evoked current amplitude in mouse hippocampal neurons. Additionally, ASIC2a interacted with the neuronal synaptic scaffolding protein PSD-95, and PSD-95 reduced cell surface expression and current amplitude in ASICs that contain ASIC2a. Overexpression of PSD-95 also reduced acid-evoked current amplitude in hippocampal neurons. This result was dependent upon ASIC2 since the effect of PSD-95 was abolished in ASIC2-/- neurons. These results lend support to an emerging role of ASIC2 in the targeting of ASICs to surface membranes, and allows for interaction with PSD-95 to regulate these processes.